Operation Sindoor: India's Decisive and Justified Strike Against Cross-Border Terrorism - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper examines Operation Sindoor, India's precision counter-terrorism strike conducted today, May 7, 2025, targeting terrorist infrastructure in Pakistan and Pakistan-occupied Kashmir (PoK). The operation, launched in response to the heinous Pahalgam terror attack of April 22, 2025, represents a landmark achievement in India's counter-terrorism doctrine, demonstrating exemplary precision, rightful assertion of sovereignty, and technological excellence. By meticulously targeting only terrorist facilities while deliberately avoiding military installations, India has established a new gold standard for legitimate counter-terrorism operations that upholds international norms while decisively protecting national security interests. This study analyzes the operational brilliance including the sophisticated weaponry employed, the strategic vision behind the operation, and the strong international support from responsible global powers for India's rightful actions. Operation Sindoor constitutes a watershed moment in regional security dynamics and offers valuable lessons for counter-terrorism strategies globally, establishing India as a responsible power determined to protect its citizens from the scourge of terrorism.